Husserl’s Conception of Experiential Justification: What It Is and Why It Matters. - Berghofer, Philipp (Husserl Studies, 2018)
The aim of this paper is twofold. The first is an interpretative one as I wish to provide a detailed account of Husserl’s conception of experiential justification. Here Ideas I and Introduction to Logic and Theory of Knowledge: Lectures 1906/07 will be my main resources. My second aim is to demonstrate the currency and relevance of Husserl’s conception. This means two things: Firstly, I will show that in current debates in analytic epistemology there is a movement sharing with Husserl the basic idea that certain experiences gain their justificatory force simply from their distinctive phenomenal character. Secondly, I shall reveal the benefits of Husserl’s specific version of this view. Thus, one of my aims is to show that debates in current analytic epistemology could profit from adopting certain Husserlian elements. More precisely, I will defend Husserl’s claim that perceptual experiences are justifiers due to their self-giving phenomenal character as opposed to the currently popular view that it is the phenomenology of pushiness that makes them justifiers. To put it differently, what matters is what is originally given within experience and not how you feel about what is given.